Usage of technological resources for the english teaching and learning process to students from atahualpa high school - Bravo Torres, Gabriela Estefanía (Machala : Universidad Técnica de Machala, 2016)
The purpose of this research was to include the use of technological resources in the english teaching learning process for students from the educational unit atahualpa, in order to achieve the highest quality in the teaching learning process of a foreign language like is english. according to our recent study has made possible to know that the teaching english without access to technology, supports a range of educational paradigms and problems even when we are learning new languages that we find it very difficult, in most cases that’s boring, is to say that when teacher do not use technology as a teaching tool, it will demonstrate that there is not motivation, dissatisfaction and boredom causing the confusion of students from english classes. also that reflects some teachers have a paper purchased, or sometimes they are untrained and they are not looking for a solution as to teach better, to create an effective learning to their students. however, this draft introduces the master trainers in the english language to the increased need to replacing and monopolizing their own education materials to integrate virtual tools and internet that we have nowadays, as a result it increases motivation.this research is kind of bibliographic. i will demonstrate a wide range of technological resources which are necessary of the english teaching learning process, there are some advantages to use the technological resources, teachers role on the application the technological resources, kind of technological resources such as; use of icts, webquest, microblogging, podcast, among others.
Keywords: USAGE; TECHNOLOGICAL; RESOURCE; ENGLISH; LEARNING; TEACHING; STUDENT; TECHNOLOGY; TEACHER